Sunlight–derived vitamin D affects interleukin-4 level, T helper 2 serum cytokines, in patients with Graves' disease: a prospective cohort study (Medical Journal of Indonesia, 2015)
Background: Graves' disease (GD) is the most common autoimmune disease leading to hyperthyroidism. The role of Th1/Th2 pathways balance in GD is still controversial. Vitamin D is reported to have an effect on those pathways. This study aims to examine the effect of sunlight exposure on vitamin D 25(OH) level and Th1 and Th2 pathway-derived cytokines in GD patients. Methods: A prospective cohort study was conducted on 32 GD patients to compare the effect of sunlight exposure on vitamin D level and cytokines of Th1 and Th2 pathways between exposed and unexposed groups. Exposed group received sunlight exposure three times a week for 30 minutes each between 9–11 a.m for 1 month. Thyroid stimulating hormone (TSH), free thyroxin (fT4), vitamin D 25(OH), interferon-γ (IFN-γ) and interleukin-4 (IL-4) serum levels, were investigated before and after one month of sunlight exposure. Paired t-test or Mann Whitney test were used to analyze the difference between exposed and unexposed GD groups before and after sun exposure. Results: One month of sunlight exposure increased vitamin D 25(OH) level by 27.90% among exposed GD group (15.34 ng/mL to 19.62 ng/mL, p<0.001). Meanwhile, unexposed GD groupâs vitamin D 25(OH) level decreased from 20.48 ng/mL to 18.86 ng/mL (p<0.001). Increased vitamin D 25(OH) level in exposed group was not accompanied by the increase of IL-4 level after sunlight exposure. Conclusion: Sunlight exposure increases vitamin D 25(OH) serum level and may affect the level of IL-4, Th2 pathway-derived cytokine, in patients with GD. However, the role of sunlight-derived vitamin D on IFN-γ in GD patients can not be concluded in this study.